THE SULPHUR ISOTOPIC COMPOSITION OF TRACE SULPHATES IN CARBONIFEROUS BRACHIOPODS: IMPLICATIONS FOR COEVAL SEAWATER, CORRELATION WITH OTHER GEOCHEMICAL CYLES AND ISOTOPE STRATIGRAPHY - Kampschulte A.; Bruckschen P.; Strauss H. (My University, 2001)
The Carboniferous δ34S record, based on the analysis of structurally substituted sulphate (SSS) in brachiopod shells, is characterized by a significant decline from values around +21±1‰ in the Tournaisian to +12±1‰ in the Gzelian. Superimposed on this broad evolution is a higher order structure with a relative minimum in the late Visean followed by a maximum in the Bashkirian.On the 107-year time scale, δ34S is positively correlated with δ13CCarb, in contrast to the long-term negative linkage between sulphur and carbon observed for the entire Phanerozoic. This indicates that mechanisms other than the redox balance control the carbon and sulphur cycles on this time scale. The 87Sr/86Sr and δ34S records display parallel trends during the Tournaisian to Moscovian. This positive correlation suggests that tectonics may be of importance for the evolution of δ34S on time scales of 107 years.A possible scenario to explain the co-evolution of the isotope systems and their linkage to tectonism and palaeoclimate invokes an increased nutrient supply to the oceans during periods of enhanced uplift and continental weathering. This nutrient flux may have resulted in increased burial of organic matter and enhanced bacterial sulphate reduction.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная